Analisis Perhitungan Harga Pokok Produksi (HPP) dengan Menggunakan Metode Full costing pada UMKM Ayam Geprek Boo’all Slipi Jakarta: Analysis of the Calculation of the Cost of Production Price (HPP) Using the Full Costing Method in Ayam Geprek Boo'all Slipi Jakarta MSMEs - Ashfa Azkiya Zahrah; Anggi Destari; Fita Pitria Adiyani; Nia Aulia Putri; Tatang Sutisna (Jurnal Manajemen dan Akuntansi Cakrawarti, 2026)
The objective of this research is to analyze the estimation of production expenses at UMKM Ayam Geprek Boo’all Slipi, determine the Cost of Goods Manufactured (COGM) using the full costing method, and compare the results of the simple method currently used by the business with the full costing method. Adopting a qualitative descriptive approach, this study utilizes firsthand information gathered through direct consultations with the entrepreneur. The results indicate that Ayam Geprek Boo’all Slipi still utilizes a simple calculation that overlooks fixed overhead costs, such as asset depreciation (carts and banners) and rent. Based on the calculation results,The COGM per portion using the simple method is Rp 18,469, while using the full costing method it is  Rp 18, 868 per portion, resulting in a difference of Rp 399 per portion. The full costing method provides more accurate and comprehensive results for business sustainability.